Empowering MSMEs in Indonesia through Sustainable Cash Waqf: Strategic Solutions Aligned with the SDGs - Rizal Agus; Enny Segarahati Barus; Amrin; Mukhtasar; Muhamad Noor Baihaqi bin Mokhtar (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study investigates the strategic optimization of cash waqf as an alternative Islamic social finance instrument to empower micro, small, and medium enterprises (MSMEs) in Indonesia within the framework of SDGs-oriented sustainable economic development. Theoretical framework: The study is framed within Islamic social finance theory, particularly cash waqf as a productive and sustainable instrument, combined with principles of institutional performance, trust-based governance, and MSME empowerment in a digital economy context supporting SDGs achievement. Literature review: The literature review discusses cash waqf as an Islamic social finance instrument for MSME empowerment, human capital development, and motivation in cash waqf management associated with SDGs implementation and inclusive economic growth. Methods: This research employs the Analytic Network Process (ANP) methodology to analyze interdependencies among strategic factors. Data were obtained from Kedai Wakaf MUI North Sumatra and Dompet Dhuafa Indonesia, supported by expert judgments from seven respondents representing practitioners and scholars in waqf and Islamic economics. Results: The results indicate that human resource development particularly motivation outweighs technical skills as the most critical internal solution. Marketing capabilities, especially product creativity and digital engagement, are also essential. Total sales are prioritized over profit margins as performance indicators. In increasing waqf collection, public awareness raising is slightly more influential than socialization. Externally, trust driven by transparency and accountability emerges as the primary concern, followed by economic factors and government policy support with sustainable funding aligned with SDGs priorities. Implications: These findings suggest that optimizing cash waqf for MSME empowerment requires an integrated, data-driven strategy that strengthens internal capacity, enhances digital marketing, ensures transparent governance, and aligns with supportive public policies for SDGs sustainability. Novelty: This study contributes novelty by empirically applying the ANP approach to prioritize internal and external strategic factors in cash waqf-based MSME empowerment, offering a structured decision-making perspective that integrates human resources, digital marketing, trust, policy dimensions, and SDGs-oriented Islamic social finance development.